PENERAPAN MEDIA PEMBELAJARAN IPA PAKARSA PADA MATERI SIKLUS AIR UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Cindy Weka Wulandari; Abdul Aziz Hunaifi; Muhamad Basori (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the implementation of the PAKARSA (Papan dan Kartu Rahasia / Board and Secret Cards) learning media in teaching science on the topic of the water cycle, and to examine its effectiveness in improving student learning outcomes. The research was conducted with fifth-grade students at SDN Plosorejo 1, Kediri Regency, during the second semester of the 2024/2025 academic year. The PAKARSA media is made of wooden boards and buffalo paper cards. The right side of the board displays a visual sequence of the water cycle stages evaporation, transpiration, condensation, and precipitation to support students’ conceptual understanding. The left side contains material and quiz cards used for evaluation and concept reinforcement. The study employed a descriptive quantitative approach with a One Group Pretest Posttest Design, where one group of students received tests before and after the learning activity. The instruments used were multiple choice and short-answer tests developed based on the national learning outcomes (Capaian Pembelajaran). The results showed an increase in the average score from 56.7 (pre-test) to 88.4 (post-test). The number of students achieving the minimum mastery criteria (score ≥75) increased from 4 to 19 out of 21 students. The classical learning mastery (KBK) reached 90.5%, indicating that the PAKARSA media was highly effective. Therefore, PAKARSA is proven to be an effective and engaging tool for science instruction, particularly in enhancing student understanding of the water cycle.